The economy: a Brexit vote winner?. Issue 2 (April 2016) - Tarran, Brian
Abstract : A NatCen study suggests that, in the upcoming vote on Britain's membership of the EU, economic arguments are likely to trump cultural concerns Abstract : A NatCen study suggests that, in the upcoming vote on Britain's membership of the EU, economic arguments are likely to trump cultural concerns.Brian Tarran reports